Regional moderate hyperthermia for mild-to-moderate COVID-19 (TherMoCoV study): a randomized controlled trial - Mancilla-Galindo, Javier; Kammar-García, Ashuin; Mendoza-Gertrudis, María de Lourdes; García Acosta, Javier Michael; Nava Serrano, Yanira Saralee; Santiago, Oscar; Torres Vásquez, Miriam Berenice; Martínez Martínez, Daniela; Fernández-Urrutia, Liliana Aline; Robledo Pascual, Julio César; Narváez Morales, Iván Daniel; Velasco-Medina, Andrea Aida; et al. (Frontiers in Medicine, 2023)
Background: Low-cost alternatives to prevent COVID-19 progression that are available to all patients are needed. Diverse forms of thermotherapy have been proposed to prevent progression to severe/critical COVID-19.Objective: To evaluate the efficacy and safety of local thermotherapy to prevent disease progression in hospitalized adult patients with mild-to-moderate COVID-19.Multicenter, open-label, parallel-group, randomized, adaptive trial to evaluate the efficacy and safety of local thermotherapy to prevent disease progression in hospitalized adult patients with mild-to-moderate COVID-19. Eligible hospitalized adult patients with symptoms of COVID-19 with ≤5 days from symptom onset, meeting criteria for mild or moderate COVID-19, were randomly assigned to the intervention consisting of local thermotherapy via an electric heat pad in the thorax (target temperature range 39.5-42 °C) continuously for 90 minutes, twice daily, for 5 days, or standard care. The main outcome was the proportion of patients who progressed to severe-to-critical COVID-19 or death.Patients were randomized in a 1:1 ratio through a centralized computer-generated sequence of minimization with a random component of 20%. Participants and medical staff were not blinded to the intervention.Results: One-hundred and five participants (thermotherapy n=54, control n=51) with a median age of 53 (IQR: 41-64) years were included for analysis after early stopping of recruitment due to closure of all temporal COVID-19 units (target sample size = 274). The primary outcome of disease progression occurred in 31.4% (16/51) of patients in the control group versus 25.9% (14/54) of those receiving thermotherapy (risk difference = 5.5%; 95%CI: -11.8-22.7, p=0.54). Thermotherapy was well tolerated with a median total duration of thermotherapy of 900 (IQR: 877.5-900) minutes. Seven (13.7%) patients in the control group and 7 (12.9%) in the thermotherapy group had at least one AE (p = 0.9), none causally attributed to the intervention. No statistically significant differences in serum cytokines were observed between day 5 and baseline among groups.Local thermotherapy was safe and well-tolerated. A non-statistically significant lower proportion of patients who experienced disease progression was found in the thermotherapy group compared to standard care. Local thermotherapy could be further studied as a strategy to prevent disease progression in ambulatory settings.